2019
DOI: 10.3390/cells8121545
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Plays Essential Roles in NASH Development by Modulating Multiple Target Proteins

Abstract: Pin1 is one of the three known prolyl-isomerase types and its hepatic expression level is markedly enhanced in the obese state. Pin1 plays critical roles in favoring the exacerbation of both lipid accumulation and fibrotic change accompanying inflammation. Indeed, Pin1-deficient mice are highly resistant to non-alcoholic steatohepatitis (NASH) development by either a high-fat diet or methionine–choline-deficient diet feeding. The processes of NASH development can basically be separated into lipid accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…In NASH patients, Pin1 was also associated with fibrosis. It has been shown that TGF-β, connective tissue growth factor, and the profibrogenic cytokines promoting fibrosis significantly decreased in Pin1-deficient mice, completely repressing fibrosis markers (10,18). Our study confirmed an association between serum Pin1 level and liver inflammation and fibro- sis in patients with HCV (genotype 1b) infection.…”
Section: Discussionsupporting
confidence: 85%
“…In NASH patients, Pin1 was also associated with fibrosis. It has been shown that TGF-β, connective tissue growth factor, and the profibrogenic cytokines promoting fibrosis significantly decreased in Pin1-deficient mice, completely repressing fibrosis markers (10,18). Our study confirmed an association between serum Pin1 level and liver inflammation and fibro- sis in patients with HCV (genotype 1b) infection.…”
Section: Discussionsupporting
confidence: 85%
“…Pin1 reportedly affects substrate stability, and regulates TGF-β1 expression, thus enhancing TGF-β1-mediated fibrogenesis signaling (Matsuura et al . 2010 ; Inoue et al 2019 ). In cells expressing BAFF-R H159Y , rBAFF stimulation increased the growth and survival of cells through the regulation of relevant genes including Pin1 (Secreto et al .…”
Section: Resultsmentioning
confidence: 99%
“…Pin1 retained the WW domains (residues 1-39) at the Nterminal and the PPIase domain (residues 45-163) at the Cterminals (Verdecia et al 2000;Chen et al 2018). Pin1 reportedly affects substrate stability, and regulates TGF-β1 expression, thus enhancing TGF-β1-mediated fibrogenesis signaling (Matsuura et al 2010;Inoue et al 2019). In cells expressing BAFF-R H159Y , rBAFF stimulation increased the growth and survival of cells through the regulation of relevant genes including Pin1 (Secreto et al 2014).…”
Section: Baff-r Was Significantly Upregulated On Primarymentioning
confidence: 99%
“…The difference in mouse age and the dosage of LPS, which may be the reason for our different results. In fact, except for some cancers, Pin1 also plays an important role in asthma development and in the response to microbial infection besides rheumatoid arthritis (RA), Systemic Lupus Erythematosus (SLE) and nonalcoholic steatohepatitis (NASH) (39)(40)(41)(42)(43)(44), suggesting that Pin1 is closely related to certain inflammatory reactions. Our study offers clues for understanding septic shock pathogenesis and might impact on the future diagnosis and treatment of patients with inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%